2013
DOI: 10.1002/smll.201203245
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Graphene Aptasensor for Ultra‐Sensitive Detection of Anthrax Toxin with Amplified Signal Transduction

Abstract: Detection of the anthrax toxin, the protective antigen (PA), at the attomolar (aM) level is demonstrated by an electrical aptamer sensor based on a chemically derived graphene field-effect transistor (FET) platform. Higher affinity of the aptamer probes to PA in the aptamer-immobilized FET enables significant improvements in the limit of detection (LOD), dynamic range, and sensitivity compared to the antibody-immobilized FET. Transduction signal enhancement in the aptamer FET due to an increase in captured PA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 83 publications
2
47
0
Order By: Relevance
“…Indeed, literature developing this concept has exploited one aptamer against PA63 in context with a graphene support (3436). AEGIS aptamers are expected to help implement this vision.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, literature developing this concept has exploited one aptamer against PA63 in context with a graphene support (3436). AEGIS aptamers are expected to help implement this vision.…”
Section: Discussionmentioning
confidence: 99%
“…127 For example, Kwon et al reported a novel liquid-ion gated FET using large-scale graphene micropattern nanohybrids decorated with closely packed conducting polymer nanoparticles for the detection of HIV. 127a Specifically, this closely packed nanoparticle array was composed of 20 nm carboxylated polypyrrole nanoparticles that were covalently modified with HIV-2 gp36 antigen and provided an enlarged surface area and stable sensing geometry. Therefore, the authors could detect the HIV biomarker at concentrations as low as 1 pM, which is better than any biosensor that has been reported for this particular purpose.…”
Section: Graphene–nanoparticle Hybrid Materials For Biosensing Appmentioning
confidence: 99%
“…On the other hand, Kim and coworkers demonstrated that, in addition to preserving the superb electrical properties of graphene and increasing available surface area, graphene–nanoparticle hybrids could also be designed to amplify the transduction signal, thereby further increasing the achievable LOD by a full order of magnitude. 127b In this work, the authors fabricated a FET biosensor that had networked channels of chemically reduced GO nanosheets, which were modified with aptamers specific for the detection of anthrax toxin (e.g., protective antigen) (Figure 15A). Briefly, in their design, the source/drain electrodes were formed on a networked film composed of rGO nanosheets using a shadow mask to prevent the deposition of polymeric residues during photolithography.…”
Section: Graphene–nanoparticle Hybrid Materials For Biosensing Appmentioning
confidence: 99%
“…, immunoglobulins), where selectivity was enabled through antibody-antigen [62,63,64,65] or protein-aptamer [66,67,68,69] binding at the graphene interface. Moreover, the probe biomolecules (e.g., antibodies, aptamers, ssDNAs) may be labeled on the surface of chemically modified graphene via (i) chemical linkers [65,67,70]; or (ii) conjugation with NPs adsorbed on its surface [63,64,70].…”
Section: Graphenementioning
confidence: 99%
“…Moreover, the limit of protein detection may be enhanced by reducing the effects of Debye screening on the immobilized target proteins. In particular, this has been demonstrated by Kim et al [62,68], where aptamers (short oligonucleotides) were utilized as probe biomolecules to achieve detection limits in the femto- and atto-molar ranges.…”
Section: Graphenementioning
confidence: 99%